Integrating gender into shock responsive and adaptive social protection approaches: Insights from a cross-regional dialogue - Jaskolski, Martina; Caroli, Giulia; Palou, Nohelia; Penel, Charlotte; Maviza, Gracsious; Takaindisa, Joyce; Campbell, Raramai (2025)
This policy brief provides insights into gender- and shock-responsive social protection approaches from Honduras, Jordan, and the Caribbean